New Era, New Thinking, New Journey of Education Reform - Zhu , Meijuan (Journal of Theory and Practice of Contemporary Education, 2023)
In the 40 years of reform and opening up, China has made brilliant achievements that have attracted the attention of the world: the Chinese people's life has achieved a leapfrog transformation from poverty to food and clothing, and then to the overall well-off society; Chinese society has undergone a historic change from being closed, poor, backward and lacking vitality to being open, prosperous, strong, civilized and full of vitality; China's economy has achieved sustained and rapid growth. Its GDP has increased from 370 billion yuan in 78 years to 82.7 trillion yuan in 2017. Its total economic output ranks second in the world, and its contribution rate to world economic growth exceeds 30%, ranking first in the world. China has become the world's largest industrial country, the largest service industry country and the largest trading country. This article will talk about the experience of great achievements made in the 40th anniversary of reform and opening up and how to start a new journey of reform.